Perancangan Konten Ilustrasi Instagram Rumah Generasi Pemenang Sebagai Upaya Membangun Kesadaran Keagamaan - Pranoto, Rasyadan; Mahimma Romadhona (Journal of Creative Student Research, 2023)
This research aims to develop an approach to designing effective illustration content on the Instagram account of the Rumah Generasi Pemenang Foundation, with a primary focus on efforts to build religious awareness among its followers. The research methodology involves analyzing the needs of the target audience, studying social media visual trends, and exploring the religious values desired by the foundation. By combining design methods and research, this study produces a series of creative and captivating illustration content, with an emphasis on delivering religious messages that can stimulate reflection and spiritual awareness. Evaluation is carried out through response tests from the target group and monitoring online interactions. The research findings show that the design of illustration content on the Instagram of Rumah Generasi Pemenang significantly contributes to increasing religious awareness among followers. The practical implications include the application of more targeted design strategies in conveying religious messages through social media, as well as providing insights to practitioners and researchers about the potential of Instagram as an effective tool in building religious awareness in the digital era.Keywords: religious awareness, social media, illustration